The Potential Flow Interactive Teaching Tool (PFITT) - Abd Razak, Azli; Suhaime, Schufee Amani; Jerai@Junaidi, Fauziah (2025)
Potential flow theory is a fundamental concept in fluid mechanics but is often challenging for students to visualize due to its mathematical complexity and reliance on ideal assumptions. To address this educational barrier, the Potential Flow Interactive Teaching Tool (PFITT) was developed as a webbased, interactive simulation platform that helps learners explore and understand the behavior of ideal flows. Built using Python and Streamlit, PFITT allows users to manipulate parameters of elementary flows such as uniform flow, source, sink, vortex, and doublet, as well as simulate their superpositions. The tool dynamically generates streamlines, stream function, and potential function plots based on user inputs, reinforcing key concepts such as flow symmetry, stagnation points, and scalar field orthogonality. The accuracy of PFITT was verified through case studies and compared against analytical solutions, showing strong agreement with theoretical expectations. With its clean user interface, real-time outputs, and browser-based accessibility, PFITT serves as a practical and scalable educational tool for enhancing conceptual understanding in fluid mechanics courses. Future enhancements may include extended flow scenarios, result exporting features, and integration with online learning platforms.